PENGEMBANGAN VIDEO PEMBELAJARAN IPA BERBASIS ANIMAKER PADA MATERI SIFAT DAN PERUBAHAN WUJUD BENDA KELAS IV SEKOLAH DASAR - Br PA, Rita Herlina (JURNAL CURERE, 2024)
The objectives of this research consist of (1) to determine the validity of the product in developing Animaker-based science teaching videos on material on the properties and changes in shape of objects in elementary schools (2) To find out the effectiveness of developing Animaker-based science teaching videos on material on the properties and changes in shape of objects in elementary schools. elementary school. This type of research is the Research and Development (R&D) ADDIE model. Data collection techniques were used with questionnaires. After analyzing the data on the research results, validation results were obtained by validator lecturers regarding the development of Animaker-based science learning videos from media expert validators, namely 82.5%, in the Very Valid category, from validation by material expert lecturers, namely, 85%, in the Very Valid category. . Meanwhile, data analysis on effectiveness was carried out by fourth grade elementary school teachers and obtained results of 94.66% in the Very Effective category.